2011
DOI: 10.1007/s12639-011-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Centenary celebrations article

Abstract: There is an urgent need for new drugs against malaria, which takes millions of lives annually. Cysteine proteases are potential new drug targets, especially when current drugs are showing resistance. Falcipains and vivapains are well characterized cysteine proteases of P. falciparum and P. vivax, respectively. Studies with cysteine protease inhibitors and manipulating cysteine proteases specific genes have suggested their roles in hemoglobin hydrolysis. In P. falciparum, falcipain-2 and falcipain-3 are major h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 53 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…FPs possess some unique structural domains as compared to other papain-like cysteine proteases. The N-terminal part of the prodomain functions in trafficking of FPs to the food vacuole and the C-terminal part of prodomain acts as an inhibitor of the mature domain, like other cysteine proteases of the C1 family ( Pandey, 2011 ). However, FPs possess short N-terminal extensions (about 12 aa) of the mature domain which is critical for folding of the mature domain to active enzyme ( Figure 5 ).…”
Section: Falcipains Unique Cysteine Proteases With Hemoglobin Bindinmentioning
confidence: 99%
“…FPs possess some unique structural domains as compared to other papain-like cysteine proteases. The N-terminal part of the prodomain functions in trafficking of FPs to the food vacuole and the C-terminal part of prodomain acts as an inhibitor of the mature domain, like other cysteine proteases of the C1 family ( Pandey, 2011 ). However, FPs possess short N-terminal extensions (about 12 aa) of the mature domain which is critical for folding of the mature domain to active enzyme ( Figure 5 ).…”
Section: Falcipains Unique Cysteine Proteases With Hemoglobin Bindinmentioning
confidence: 99%
“…Cysteine protease inhibitors have been proposed as antimalarial drugs, because of the critical role for these proteases in hemoglobin hydrolysis at the trophozoite stage of malaria parasite [197]. These proteases also take part in many human physiological pathways such as antigen processing and prohormone activation, as in some diseases including arthritis, Alzheimer’s disease, and cancer-cell invasion, reinforcing the importance of finding new cysteine protease inhibitors.…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…Among falcipain family cysteine proteases, key enzymes in erythrocytic parasites appear to be falcipain-2 (FP2) and falcipain-3 (FP3), which are major hemoglobinases of P. falciparum , and in P. vivax , vivapain-2 (VP2), vivapain-3 (VP3) and vivapain-4 (VP4) [4] . Structural and biochemical analysis of falcipains showed that they have specific domains with defined functions.…”
Section: Introductionmentioning
confidence: 99%